Elizabeth I & the Spanish Armada - Hynson, Colin (Columbus, OH : School Specialty Pub., 2006)
Presents an account of the reign of England's Queen Elizabeth I, in graphic novel form, focusing on her role in defending her country against the Spanish armada.
Includes index.
Cover title: Elizabeth I and the Spanish Armada.
3.7
3-6
Keywords: Great Britain -- History, Naval -- Tudors, 1485-1603 -- Comic books, strips, etc. -- Juvenile literature; Armada, 1588 -- Comic books, strips etc. -- Juvenile literature; Elizabeth -- I, -- Queen of England, -- 1533-1603 -- Comic books, strips, etc. -- Juvenile literature; Great Britain -- History, Naval -- Cartoons and comics; Elizabeth -- I, -- Queen of England, -- 1533-1603 -- Cartoons and comics; Armada, 1588 -- Cartoons and comics; Cartoons and comics; Great Britain -- History -- 1485-1603, Tudors -- Comic books, strips, etc; Elizabeth -- I, -- Queen of England, -- 1533-1603 -- Comic books, strips etc; Spanish Armada, 1588 -- Comic books, strips etc; Comic books, strips, etc